Eksplorasi Keanekaragaman Jamur Edible di Pasar Jakarta dan Bekasi: Potensi Pangan Fungsional dan Bioaktivitasnya - Angela, Ezra; Purba, Dian Pirma Natasari; Siahaan, Frisca Olivia; Situmorang, Agnes Feronika; Hutabarat, Anne Serafin; Mamangkey, Jendri; Sunarto (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Biodiversity, especially edible mushrooms, plays a crucial role in food sustainability and public health. Edible mushrooms, such as Shiitake and oyster mushrooms, are known to be rich in nutrients and bioactive compounds that are beneficial for health, including antioxidant and anticancer effects. This research aims to identify various types of edible mushrooms sold in traditional and modern markets in several areas of Jakarta and Bekasi, as well as to evaluate their potential as sources of functional food and biopharmaceuticals. The exploration method was conducted through direct visits to several markets, where data was collected and analyzed descriptively. The results indicate that there are 10 species of edible mushrooms in the Jakarta area and 8 species in Bekasi, with ear mushrooms and oyster mushrooms being the most commonly found. Public knowledge regarding the health benefits of edible mushrooms is still limited, thus this research is expected to raise awareness about the importance of utilizing edible mushrooms as part of a healthy diet and their potential in the food and health industry. Public awareness related to a healthy diet, edible mushrooms can be used as an attractive alternative in natural medicine and nutrition, supporting food sustainability in Indonesian society.